Propuesta de mejoramiento en el área de operaciones para la empresa pública municipal mancomunada de agua potable, alcantarillado y servicios integrales del manejo de residuos sólidos, urbanos y rurales de los cantones de Bolívar, Junín, San Vicente, Sucre y Tosagua (EMAARS-EP), para el año 2014. - Mendoza Macías, Yoviry Ricardo (2014)
The Present investigation has as composition to create of a “Proposal of improvement in the area of operations for the enterprise public municipal community of water potable, sewers and service integral of the handling of residues solid, urban and rural of Bolivar, Junín, San Vicente, Sucre y Tosagua (EMAARS-EP) for the year 2014”; the methodology diligent in the investigation pertaining to the method scientific, the induction, the method descriptive and the technical statistical. This investigation is realize, due to that the enterprise is the axis fundamental in the production and distribution of the water potable for the collectivity of the city renowned. After of the application of the methodology select, that permitted to attain the objective of the investigation, was deduced what is necessary to improve the process operational; was analyzed the conditions present, deducing what the best option is to produce more water potable of quality for to guarantee a best service, besides of make plains of the care of water that help to improve the collection; with one advantage additional that is, to guarantee the satisfaction of the client and the survival in the time.